Genetic and pharmacological targeting of CSF-1/CSF-1R inhibits tumor-associated macrophages and impairs BRAF-induced thyroid cancer progression. - Mabel Ryder; Matti Gild; Tobias M Hohl; Eric Pamer; Jeff Knauf; Ronald Ghossein; Johanna A Joyce; James A Fagin (PLoS ONE, 2013)
Advanced human thyroid cancers are densely infiltrated with tumor-associated macrophages (TAMs) and this correlates with a poor prognosis. We used BRAF-induced papillary thyroid cancer (PTC) mouse models to examine the role of TAMs in PTC progression. Following conditional activation of BRAF(V600E) in murine thyroids there is an increased expression of the TAM chemoattractants Csf-1 and Ccl-2. This is followed by the development of PTCs that are densely infiltrated with TAMs that express Csf-1r and Ccr2. Targeting CCR2-expressing cells during BRAF-induction reduced TAM density and impaired PTC development. This strategy also induced smaller tumors, decreased proliferation and restored a thyroid follicular architecture in established PTCs. In PTCs from mice that lacked CSF-1 or that received a c-FMS/CSF-1R kinase inhibitor, TAM recruitment and PTC progression was impaired, recapitulating the effects of targeting CCR2-expressing cells. Our data demonstrate that TAMs are pro-tumorigenic in advanced PTCs and that they can be targeted pharmacologically, which may be potentially useful for patients with advanced thyroid cancers.